PENGEMBANGAN BAHAN AJAR APRESIASI SENI UKIR TRADISIONAL TORAJA BAGI SISWA SEKOLAH MENENGAH TINGKAT ATAS DI TORAJA UTARA (TAHAP PENGEMBANGAN/UJICOBA) - Tangsi, Tangsi; Husain, Muhammad Saleh; Salam, Sofyan (Nuansa Journal of Arts and Design, 2024)
This study focuses on developing teaching materials for appreciating traditional Toraja wood carving art for senior high school students in North Toraja Regency. The teaching material is presented in a booklet titled Getting to Know Toraja Wood Carving Art, aimed at testing its practicality and effectiveness. The subjects of this study were 20 senior high school students who agreed to participate in the trial use of the booklet. The participants consisted of 13 students from Senior High Schools (SMA) and 7 students from Vocational High Schools (SMK). The collected data were analyzed with the following results: (1) The Getting to Know Toraja Wood Carving Art booklet was effective in teaching Senior High School (SMA) students but not yet effective for Vocational High School (SMK) students; (2) The booklet was considered practical as a learning resource for both SMA and SMK students; (3) The booklet is deemed suitable for broader trials with SMA students. However, for SMK students, the booklet needs revision. It is recommended that relevant authorities facilitate follow-up actions related to the Getting to Know Toraja Wood Carving Art booklet.